Cytokine Diedel and a viral homologue suppress the IMD pathway in Drosophila - Lamiable, Olivier; Boutros, Michael (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Viruses are obligatory intracellular parasites that suffer strong evolutionary pressure from the host immune system. Rapidly evolving viral genomes can adapt to this pressure by acquiring genes that counteract host defense mechanisms. For example, many vertebrate DNA viruses have hijacked cellular genes encoding cytokines or cytokine receptors to disrupt host cell communication. Insect viruses express suppressors of RNA interference or apoptosis, highlighting the importance of these cell intrinsic antiviral mechanisms in invertebrates. Here, we report the identification and characterization of a family of proteins encoded by insect DNA viruses that are homologous to a 12-kDa circulating protein encoded by the virus-induced Drosophila gene diedel (die). We show that die mutant flies have shortened lifespan and succumb more rapidly than controls when infected with Sindbis virus. This reduced viability is associated with deregulated activation of the immune deficiency (IMD) pathway of host defense and can be rescued by mutations in the genes encoding the homolog of IKKγ or IMD itself. Our results reveal an endogenous pathway that is exploited by insect viruses to modulate NF-κB signaling and promote fly survival during the antiviral response.